Determination of Mercury in an Assortment of Dietary Supplements Using an Inexpensive Combustion Atomic Absorption Spectrometry Technique. Issue 4 (11th December 2005) - Levine, Keith E.; Levine, Michael A.; Weber, Frank X.; Hu, Ye; Perlmutter, Jason; Grohse, Peter M.
Abstract : The concentrations of mercury in forty, commercially available dietary supplements, were determined using a new, inexpensive analysis technique. The method involves thermal decomposition, amalgamation, and detection of mercury by atomic absorption spectrometry with an analysis time of approximately six minutes per sample. The primary cost savings from this approach is that labor-intensive sample digestion is not required prior to analysis, further automating the analytical procedure. As a result, manufacturers and regulatory agencies concerned with monitoring lot-to-lot product quality may find this approach an attractive alternative to the more classical acid-decomposition, cold vapor atomic absorption methodology. Dietary supplement samples analyzed included astragalus, calcium, chromium picolinate, echinacea, ephedra, fish oil, ginger, ginkgo biloba, ginseng, goldenseal, guggul, senna, St John's wort, and yohimbe products. Quality control samples analyzed with the dietary supplements indicated a high level of method accuracy and precision. Ten replicate preparations of a standard reference material (NIST 1573a, tomato leaves) were analyzed, and the average mercury recovery was 109% (2.0% RSD). The method quantitation limit was 0.3 ng, which corresponded to 1.5 ng/g sample. The highest found mercury concentration (123 ng/g) was measured in a concentrated salmon oil sample. When taken as directed by an adult, this product would result in an approximate mercury ingestion of 7 μ g per week.